Conceptual design and assessment of turboelectric and hybrid electric propulsion system architectures for civil transport aircraft. - Tashie-Lewis, Bernard Chukwudi (Cranfield University, 2018)
To achieve ambitious future environmental targets for aircraft set out by organisations such as NASA and the European Union, turboelectric distributed propulsion (TeDP) has been proposed as a novel concept that has the potential to achieve these targets by significantly improving integrated propulsion-airframe performance. Realising TeDP as a technology option brings into play a number of design and development challenges due to the highly integrated natured of TeDP-airframe configurations, low technology-readiness-levels of key enabling technologies and new modes of operation opened up by shift to a more electric architecture. In tackling these challenges a multidisciplinary and integrated method to assess the benefits and challenges of turboelectric and hybrid-electric propulsion system configurations by considering the effect of aircraft size, mission specifications, airframe, electrical system, energy storage, propulsor architecture and gas turbine architecture was created. The method created was used in the assessment of turboelectric and hybrid electric performance for a regional transport aircraft and a medium haul transport aircraft. For the regional role the employment of a DC hybrid superconducting turboelectric architecture managed to achieve 16.7% block fuel saving and 3.23% total energy consumption saving over a baseline turboprop aircraft at 600 n.mi range. Driving performance benefits was increased duration of mission time batteries spend discharging at relatively high battery power rating which overcomes weight penalties from installation of electric machinery. For medium haul role the employment of a geared hybrid electric architecture managed to achieve a 3.07% block fuel saving over a baseline turbofan aircraft at 900 n.mi range. Driving performance benefit for the mission was increased battery-operative-cruise time at relatively high battery power rating overcoming aircraft weight penalty and electric machinery installation weight penalty. Despite fuel burn reduction, hybrid electric aircraft consumes more energy than a baseline configuration primarily due to utilisation of additional energy from battery pack.
Keywords: DC; TeDP; HeP; HeDP; HTS; superconducting; hydrogen; battery; energy storage; propulsor; propellor; gas turbine; CADI; ducted fan